Agent empowerment and its influence on perceived fairness of service in hospitality customer service program interactions - Delos Reyes, Ron Louie (Southeast Asian Journal of Service Management, 2026)
The Business Process Outsourcing (BPO) industry in the Philippines has experienced fast expansion which created various job openings that mainly focus on hotel reservation customer service work. The BPO sector needs agents to receive decision-making authority together with complete training and role confidence in delivering better service. The process which companies provide to their customers leads to better customer fairness which supports Sustainable Development Goal 8: Decent Work and Economic Growth. The research also investigates how agents gain empowerment through their positions and deliver equivalent service by performing their duties across three service dimensions which includes outcome-based, process-based and interactional dimensions. This research investigates how job satisfaction affects the delivery of services in organizations and agents who experience empowerment tend to view both results and operational methods as being just and equitable. Different levels of interactional fairness because their organizations support them and their relationships with colleagues at work. Job satisfaction is the primary mediator which leads employees to become involved while delivering services that are both uniform and fair to all customers. The hospitality BPO operations need strategic empowerment initiatives to establish their fundamental operations which result in sustainable success and equal service delivery while building sustainable economic growth.